2022
DOI: 10.1002/htj.22616
|View full text |Cite
|
Sign up to set email alerts
|

Numerical study of Williamson hybrid nanofluid flow with thermal characteristics past over an extending surface

Abstract: The energy and mass dissemination rate have been studied through Williamson hybrid nanofluid (NF) flow comprised of silver (Ag) and magnesium oxide (MgO) nanoparticles (NPs) past over an extending porous surface.The hybrid nanofluid has synthesized by dispersion of Ag and MgO nanoparticles in the base fluid (engine oil). The effects of the constant magnetic field, thermal dissipation, and heat source are also studied in the present analysis. The above scenario has been designed in the form of a nonlinear syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 52 publications
0
18
0
Order By: Relevance
“…The Cauchy stress tensor ( S) for the Williamson nanofluid is defined as (Alhowaity et al, 2022b) where (μ 0 , μ ∞ ) → limiting viscosity at zero and at an infinite shear rate, respectively, τ → extra stress tensor,…”
Section: Conservation Equation Of the Nanoparticle Concentrationmentioning
confidence: 99%
See 1 more Smart Citation
“…The Cauchy stress tensor ( S) for the Williamson nanofluid is defined as (Alhowaity et al, 2022b) where (μ 0 , μ ∞ ) → limiting viscosity at zero and at an infinite shear rate, respectively, τ → extra stress tensor,…”
Section: Conservation Equation Of the Nanoparticle Concentrationmentioning
confidence: 99%
“…Freezing temperature is studied in aluminum oxide nanofluid magnetic flow with a radiative effect in the study by AdnanKhan and Ahmed (2022). Nanofluids flow with a variety of forces and characteristics, which have been studied for the rate of heat transfer are in the research studies by Khan et al (2019a); Shah et al (2019); Ahmed et al (2020); Khan et al (2021a); Ashraf et al (2022); Alhowaity et al (2022b).…”
Section: Introductionmentioning
confidence: 99%
“…A hybrid nanofluid is a new type of fluid that outperforms when compared to regular fluids, such as ethyl alcohol, water, nanofluids, and ethylene, during energy transitions. HNFs have a huge spectrum of thermal properties, including the ability to freeze at high temperatures [18][19][20]. Hybrid NFs are used in energy generation, heat transfers, heat pumps, air conditioners, the automotive industry, electrical appliances, turbines, nuclear reactors, broadcasting, spacecraft, and biotechnology [21].…”
Section: Introductionmentioning
confidence: 99%
“…With regard to this statement, Rashid et al 35 explored the research on viscous fluid flow over a nonlinearly stretching sheet and found that the flow features revealed many interesting behavioral aspects that confirmed further study of the effects of nonlinear stretching on the flow characteristics is warranted. Alhowaity et al 36 investigated the homotopy perturbation method and axisymmetric flow over a stretching sheet, and comparison of their results with the exact solutions showed that the homotopy perturbation method gives outstanding results. The analysis of Bilal et al 37 of temperature field inflow over a stretching sheet with uniform heat flux showed that the temperature at a point declines with an upsurge in the Prandtl number.…”
Section: Introductionmentioning
confidence: 99%